ปัจจัยทางเศรษฐกิจมหภาคที่มีผลต่ออัตราผลตอบแทนของดัชนี ราคาหุ้นกลุ่มพลังงานโดยวิธีถดถอยแบบควอนไทล์ - ศราวุฒิ ชุมภูอินตา (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The objectives of this study is to analyze the macroeconomic factors affecting rate of returns on price index of energy securities using quantile regression at quantile level 0.25, 0.5 and 0.75. The results will be used to evaluate the effect of macroeconomic factors affecting rate of return on price index of energy securities on different quantile levels. A secondary data in quarterly was carried on since the first quarter of 2004 to the fourth quarter of 2014 that consisted of interest rates, the rate of change in foreign currency exchange rates, inflation and the rate of change in crude oil prices in Dubai as the independent variable and the rate of return on price index of energy securities as the dependent variable. The result for unit root test showed all variables to be stationary at Level or I(0). After using quantile regression, it was indicated that the rate of change in crude oil prices in Dubai was positively related with the rate of return on price index of energy securities at quantile level 0.25, 0.5 and 0.75 and the effect was increased when the rate of return on price index of energy securities increased. The interest rates were negatively related with the rate of return on price index of energy securities at quantile level 0.5. The other variables were insignificant. Therefore, investors should pay attention to the rate of change in crude oil prices in Dubai at all quantile levels or all the levels of the rate of return on price index of energy securities. As for interest rate, investors should pay attention to the rate of return at the medium level on price index of the medium level energy securities.